THE E-BIKE PATH: LEGAL APPROACH IN EUROPEAN UNION LAW - Alina Mihaela CONEA (Challenges of the Knowledge Society)
Are there simple thinks that anyone can do and that can change our world? Some says that using bikes in our cities will make us healthy, more focused and smart, happy, living in cleaner environment, having safer roads and a lively urban life. E-bikes are becoming more present in our cities and in our lives. One question is how the legal world is coping with new technologies and societal trends. A bicycle with a little e- is just a bike? According to European Union law, the answer is sometimes yes and sometimes no, since the legal definition of e-bikes is not to be found, whatsoever, in the EU legal acts. As compare to regular bicycles, electrical bicycles are within the scope of by Internal Market legislation. The present paper is concisely address the relevant legal acts applying to e-bikes, the terminology used, the rules governing the use of e-bikes and the ongoing debate related to insurance against civil liability in respect of the use of motor vehicles. E-cycling is seen as an integral part of the transport systems of the future. This electrical bike legal insight can help us take a brief ride through some of the EU policies: transport, internal market, competition, health, energy and smart cities.